Hastag War on Social Media: Unraveling Framing Strategies in the Duel #2019GantiPresiden Vs. #DiaSibukKerja - Nawiruddin; Sirojuddin Aly; Agus Nugraha; Siska Armawati Sufa; M. Wiranata Pratama (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Social media has emerged as the primary avenue for individuals to articulate their political and social stances. Hashtag wars, a prevalent phenomenon, witness divergent groups utilizing hashtags to promote their agendas and express viewpoints. Within the political realm, these hashtag battles often serve as arenas for discourse and mass mobilization. This study aimed to unveil the framing strategies employed in the hashtag war between #2019GantiPresiden and #DiaSibukKerja on social media. Utilizing a content analysis approach, the research scrutinizes hashtag usage, conveyed messages, and user responses. Various framing techniques, including episodic and thematic framing, alongside positive and negative framing, are analyzed. Moreover, the research explores the influence of social media usage and user interactions on the dissemination of political messages during hashtag wars. Findings indicate the dominance of #2019GantiPresiden in the social media hashtag war. The framing strategies and political discourse of both hashtags serve distinct purposes. #2019GantiPresiden utilizes sentiment-driven or provocative language to highlight dissatisfaction with Jokowi's leadership, while #DiaSibukKerja underscores Jokowi's achievements, emphasizing stability and success. In terms of hashtag impact, #2019GantiPresiden effectively influences public opinion and garners widespread support. Conversely, #DiaSibukKerja succeeds in portraying Jokowi's leadership positively. The practical implications of this research can aid stakeholders in politics and social media to comprehend effective framing techniques for disseminating political messages through digital platforms.